Pentingnya Edukasi Seks Pada Anak Sedari Dini: Studi Kasus Terhadap Anak Korban Pelecehan Seksual - Akmalia, Navissa; Amanah, Fisa (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
In this modernization era, sexual violence increasing greatly especially in school-aged children. Sexual violence is any sexual act, attempt to obtain a sexual act, or other act directed against a person’s sexuality using coercion, by any person regardless of their relationship to the victim, in any setting(WHO, 2021). The purpose of this research is to explore parents’ perspective of sexual education, in which often known as taboo. This research used qualitative case study method, with Miles Huberman data analysis.Qualitative data were obtained from three children (7-10 years old) and the parents. The results showed that parents have limited knowledge toward sex education to their children. This also happened because sexuality considered as taboo topics for children. Parents are expected to give a proper sexual education to their children based on their developmental stages.